Development of a Network to Mitigate Risk Factors Based on Buddhist Principles in Lampang and Nan Provinces - Chaiwong, Silawat; Chirakitnimit, Nadthanon; Phrakrusiridhamabundit; Phuriwattano, Phrakrusangkarak Suphanut; Boonnad, Manoon; Kaewlangka, Theerawat (Journal of International Buddhist Studies, 2024)
The objective of the study to develop a network to mitigate risk factors based on Buddhism principles in Lampang and Nan provinces is to develop and promote a gauging model to evaluate networks to mitigate risk factors according to the “Baworn” principle in Lampang and Nan provinces. It is intended to develop the environment and management guidelines for the novices’ network, mitigate risk factors in the areas of Lampang and Nan provinces, as well as to propose a policy for the provincial-level Sangha Council to build a comprehensive risk factor reduction network mechanism for the related Sangha administrative, public health, and local government organizations. The methodology used in this study utilizes a mixed research method. The result of the study revealed that the 40 participating temples in both provinces had yielded 4 indicators, comprising: the 1st indicator being the implementation according to the Sangha Supreme Council and in accordance with the country’s laws, the 2nd indicator being the policy based on evaluations, the 3rd indicator includes organizing activities that are related to the mitigation of risk factors, and finally, the 4th indicator being the network partners. All of the 40 indicators were evaluated before and after the activities. The study revealed that most of the networks carried out their activities based on the established indicators for the development of the environment and network management guidelines.